A Visualizing Study of Blister Initiation Behavior by Gas Decompression - Atsushi Koga (Japanese Society of Tribologists, 2013)
This study presents the effects of the type of polymer and gas on blister fracture in terms of visualizing O-ring behavior under high-pressure gas. To visualize blisters (internal cracks) by optical microscopy, transparent EPDM and VMQ O-rings were molded, and a special viewable high-pressure vessel with a glass viewport was developed. The O-ring specimens were exposed to high-pressure hydrogen, helium, and nitrogen gases at 10 MPa under room temperature, 25°C, after which these gases were rapidly decompressed for 0.3 seconds. The blister fracture occurred in EPDM but not in VMQ even though the two materials had the same Young's modulus. It is presumed by AFM observation that the difference in microstructure at sub-micrometer level between EPDM and VMQ influenced their blister initiation. The blister damage of the transparent EPDM O-ring in nitrogen gas was the most serious, while that in the helium gas was the slightest. The reason why the blister damage of the O-ring in the helium gas was the slightest is considered to be because solute helium gas diffused out from the O-ring after decompression faster than the other gases.